Plants send small RNAs in extracellular vesicles to fungal pathogen to silence virulence genes - Cai, Qiang; Qiao, Lulu; Wang, Ming; He, Baoye; Lin, Feng-Mao; Palmquist, Jared; Huang, Sienna-Da; Jin, Hailing (Science (American Association for the Advancement of Science), 2018)
Some pathogens and pests deliver small RNAs (sRNAs) into host cells to suppress host immunity. Conversely, hosts also transfer sRNAs into pathogens and pests to inhibit their virulence. Although sRNA trafficking has been observed in a wide variety of interactions, how sRNAs are transferred, especially from hosts to pathogens and pests, is still unknown. Here, we show that host cells secrete exosome-like extracellular vesicles to deliver sRNAs into fungal pathogen These sRNA-containing vesicles accumulate at the infection sites and are taken up by the fungal cells. Transferred host sRNAs induce silencing of fungal genes critical for pathogenicity. Thus, has adapted exosome-mediated cross-kingdom RNA interference as part of its immune responses during the evolutionary arms race with the pathogen.